Demand for fentanyl becomes inelastic following extended access to fentanyl vapor self-administration. (January 2021) - McConnell, Sam A.; Brandner, Adam J.; Blank, Brandon A.; Kearns, David N.; Koob, George F.; Vendruscolo, Leandro F.; Tunstall, Brendan J.
Abstract: Opioid use disorder imposes great societal harm in the United States and in countries worldwide. Animal models that accurately capture motivational changes that occur in opioid dependence are critical to studying this disorder. The present study used a model of opioid vapor self-administration combined with a behavioral economics approach to determine whether rats would be more motivated to "work" to defend their baseline intake of fentanyl (i.e., more inelastic demand) following sufficiently frequent, intense, and chronic exposure to self-administered vaporized fentanyl. Male rats were allowed to respond for deliveries of 1.5-s of vaporized 10 mg/ml fentanyl solution. Following 15 sessions of short access (ShA; 1 h) vs. long access (LgA; 12 h) to self-administration, we conducted a between-sessions demand curve procedure, and observed significantly more inelastic demand for fentanyl (Essential Value; EV), and increased maximal response output (Omax ) in LgA compared with ShA rats. In a subsequent phase, the unit-dose was doubled to 3 s of fentanyl vaporization. After seven ShA vs. LgA sessions, we assessed demand again and found that LgA rats, contrasted to ShA rats, demonstrated significantly higher baseline intake or "hedonic setpoint" ( Q 0 ), in addition to significantly increased EV and Omax . These results demonstrate that extended access to self-administration of a vaporized opioid causes changes in behavioral economic metrics consistent with development of an addiction-like state in rats. The combination of the vapor model with a translationally relevant behavioral economics framework opens new avenues to study dysregulated motivational processes in substance use disorders. Highlights: Translationally relevant rat models of opioid use disorder are needed. Fentanyl vapor self-administration was tested using a behavioral economic framework. Rats allowed extended access developed more inelastic demand for fentanyl. This approach can facilitate studying the neurobiology of disordered motivation.